(untitled) (Research, Society and Development, 2021)
Indigenous peoples are the target of global concern in relation to Covid-19. The aim of this study was to analyze the epidemiological data of Covid-19 in the Special Indigenous Sanitary Districts (DSEI) of the state of Mato Grosso and to evaluate the importance of health education in combating the pandemic in indigenous communities. This is an observational, ecological, quantitative study carried out in November 2020 in the state of Mato Grosso. Data were collected on Covid-19 available in the public systems of the Secretariat of Indigenous Health (SESAI) notified in Special Indigenous Health Districts (DSEI), as well as the number of Basic Indigenous Health Units located in the state’s districts. Regarding the number of Basic Indigenous Health Units, the state has 176 units and 51 of them only in the District of Cuiabá. The DSEI Cuiabá incidence rate was 17,412.5 per 100,000 inhabitants. Regarding the mortality rate, DSEI Cuiabá presented 310.9 per 100,000 inhabitants. In relation to Brazil, the mortality rate was 80.2 per 100,000 inhabitants and the incidence rate was 2934 / 100,000 inhabitants. The number of Basic Indigenous Health Units (UBSI) in Mato Grosso is in line with that recommended by the Brazilian Ministry of Health, however, the mortality and incidence rates of Covid-19 in Special Indigenous Health Districts are high when compared to the rates mortality and incidence rates in Brazil. Prevention measures and health education are crucial in combating respiratory pathologies in indigenous communities in Brazil.